Avaliação do modelo HEC-HMS versão 4.1 na simulação hidrossedimentométrica de pequenas bacias. Estudo de caso na região central do Rio Grande do Sul - Valcorte, Pablo Weber (2017)
Sediments are the results of erosion, transport, deposition and compaction processes, your production causes several problems, among them, silting rivers and reservoirs and surface waters contamination. Sediment production study in a watershed and the rivers transpor is important to estimate the quantity and origin of the sediments transported, in order to plan and make better use of water resources. The reserach objective was simulate hydrosedimentometric of a small watershed, from fluviedimetric observations instaled for this purpose, where observations were made of suspended sediment concentration and background discharge measurements. The área used in the work is located in the Vacacaí Mirim basin, central region of Rio Grande do Sul, located in the municipalities of Santa Maria and Itaara. The HEC-HMS 4.1 software was used to make the simulation and the observed data were used for its calibration and validation. The results found in the flow simulation were considered satisfactory for two sub-basins analyzed with Nash-Sutcliffe coefficients of 0,825 and 0,724 for calibration and 0,575 and 0,831 for validation, however for the other sub-basin analyzed the calibration and validation results were not considered acceptable, 0,573 and 0,335. In relation to sediment production, it was possible to observe that the highest production occurred in the summer season, with average values of 118,49, 3,97 and 3,86 ton/day for total sediments and 8,54, 0,31 and 0,18 ton/day for suspended sediments because it presentes higher amount of precipitations and the smaller production in the winter season, beacause it is where it presents the least amount of precipitations. The results of the sediment simulation, compared to the observed data in other studies showed that the simulated values are of the same order of magnitude as those observed for the suspended sediment.